Development and testing of a cryogenic induction motor with a novel Dewar structure. (June 2021) - Ma, Enze; Wu, Hong; Li, Yulong
Highlights: A novel Dewar with partial immersion cooling is proposed and developed. The reliability of this Dewar is investigated through testing a cryogenic motor. The cryogenic motor works well during the no-load test with a slip rate of 0.02. Abstract: A Dewar is the key structure of motors with high temperature superconducting (HTS) armature windings. Traditional Dewars use total immersion cooling, which can cause additional mechanical losses and challenges for rotary sealing. To avoid these problems, a novel Dewar structure was developed with partial immersion cooling. A 15 kW cryogenic induction motor with the designed Dewar was then developed. Its stator core and the coil were cooled with liquid nitrogen through partial immersion cooling. We studied the thermal insulation performance of the Dewar, and the running performance of the cryogenic induction motor. The temperature characteristics of the stator core were measured by PT-100 temperature sensors. Results show that the stable temperature of the stator is 76.5 K. Under no-load conditions, the slip rate of the motor is 0.02 with the no-load current being 30 A at 350 V of the stator voltage. The no-load loss power at low temperature is much larger than that at room temperature. These results suggest that the partial immersion cooling is effective, which validates the reliability of the designed Dewar structure, and that running performance of the motor designed is desirable.